Action research with caseworkers: Responding to and reflecting on the impacts of COVID‐19 on birth family contact. Issue 4 (16th May 2022) - Ciftci, Sarah; Collings, Susan; Wright, Amy Conley
Abstract: Social distancing due to COVID‐19 forced changes to contact with birth relatives for children in out‐of‐home care. This required a shift to using technologies, which was previously underutilized and viewed as risky. In an action research study, 33 caseworkers in New South Wales, Australia, reflected upon adapting their practices. Three key themes characterized the changes in caseworker practices and how these impacted upon social interactions between children and their birth and carer families: communication, not location; shared not separate spaces and spontaneous not restricted interaction. First, caseworkers described how contact via technologies involved fewer logistical arrangements, shifting the focus on interactions among children and their two families and encouraging these to be flexible and child‐centred. Second, caseworkers discussed how spending time together virtually could build trust, as carers and birth relatives could forge relationships around shared commitment to the child's wellbeing. Third, caseworkers noted that technology‐facilitated communication enabled greater choice and control for children while requiring renegotiating boundaries. The findings reflect a shift in caseworker perceptions of technology‐facilitated contact from a risk to opportunity framework as a result of COVID‐19 conditions, consistent with social shaping of technology theory. Beyond the pandemic, contact with birth relatives can be enhanced through technology.